Will my child do better if she enrolls in a clinical trial?. Issue 20 (6th October 2018) - Smith, Malcolm A.; Joffe, Steven
Abstract : The question of whether children with cancer who enroll in clinical trials have superior outcomes compared with those who do not participate has been pursued for more than 4 decades, and recent studies have provided conflicting answers. Whether clinical trial participation influences outcome has important implications for how clinicians should present trial participation to patients and families. Methodological challenges limit generalizations about the impact of clinical trial participation on outcome compared with nonparticipation. Oncologists should inform patients and families that clinical trials are the engine for future progress because they identify more effective therapies and that clinical trial participation is a reasonable option to consider for children with cancer. However, as noted in by Truong and colleagues in this issue, the rationale for trial enrollment should not include an expectation of better outcomes compared with nonenrollment. Abstract : Whether children with cancer who enroll in clinical trials have superior outcomes compared with those who do not participate has important implications for how clinicians should present trial participation to patients and families. Although clinical trials are the engine for future progress in identifying more effective therapies, the rationale for trial enrollment should not include an expectation of better outcomes compared with nonenrollment. See also pages4064‐71 and4098‐106 .